Accelerometer-derived sedentary time and physical activity and the incidence of depressive symptoms – The Maastricht Study. Issue 13 (18th October 2022) - Konopka, Magdalena J.; Köhler, Sebastian; Stehouwer, Coen D. A.; Schaper, Nicolaas C.; Henry, Ronald M. A.; van der Kallen, Carla J. H.; Savelberg, Hans H. C. M.; Eussen, Simone J. P. M.; Dagniele, Pieter C.; van Dongen, Martien C. J. M.; Schram, Miranda T.; Koster, Annemarie
Abstract: Background: This study examined the associations between accelerometer-derived sedentary time (ST), lower intensity physical activity (LPA), higher intensity physical activity (HPA) and the incidence of depressive symptoms over 4 years of follow-up. Methods: We included 2082 participants from The Maastricht Study (mean ± s.d. age 60.1 ± 8.0 years; 51.2% men) without depressive symptoms at baseline. ST, LPA and HPA were measured with the ActivPAL3 activity monitor. Depressive symptoms were measured annually over 4 years of follow-up with the 9-item Patient Health Questionnaire (PHQ-9). Cox regression analysis was performed to examine the associations between ST, LPA, HPA and incident depressive symptoms (PHQ-9 ⩾ 10). Analyses were adjusted for total waking time per day, age, sex, education level, type 2 diabetes mellitus, body mass index, total energy intake, smoking status and alcohol use. Results: During 7812.81 person-years of follow-up, 203 (9.8%) participants developed incident depressive symptoms. No significant associations [Hazard Ratio (95% confidence interval)] were found between sex-specific tertiles of ST (lowest v . highest tertile) [1.13 (0.76–1.66], or HPA (highest v. lowest tertile) [1.14 (0.78–1.69)] and incident depressive symptoms. LPA (highest v. lowest tertile) was statistically significantly associated with incident depressive symptoms in women [1.98 (1.19–3.29)], but not in men ( p -interaction <0.01). Conclusions: We did not observe an association between ST or HPA and incident depressive symptoms. Lower levels of daily LPA were associated with an increased risk of incident depressive symptoms in women. Future research is needed to investigate accelerometer-derived measured physical activity and ST with incident depressive symptoms, preferably stratified by sex.